2004
DOI: 10.1209/epl/i2004-10178-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of oxide films CoFeHfO: A possible candidate for all-oxide TMR junctions?

Abstract: In search of a magnetic oxide, which is insensitive to oxygen at interfaces and thus appropriate as an electrode layer for tunneling junction applications, we prepared thin films of CoFeHfO by reactive DC-magnetron sputtering technique and investigated the relation between structural and magnetic properties. The results suggest that the films consist of two disorded phases, a Co(Fe)-rich and a HfO-rich. It was found that the degree of film homogeneity and thus the magnetic nature depends on preparation conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…For comparison, table 1 summarizes the important parameters of several films that are good candidate materials for magnetic recording and sensor applications. Obviously, the present films exhibit superior properties to the comparison films (table 1) and other films reported in the literature [10][11][12][13][14][15][16][17][18][19]. Among them, the P O2 = 11.5% sample (Co 19.35 Fe 53.28 Hf 7.92 O 19.35 ) exhibits the softest magnetic properties (4π M s = 19.86 kG and H cE = 1.5 Oe) together with a high electrical resistivity (ρ = 3569 μ cm).…”
Section: Magnetic and Electrical Properties 321 Effects Of Partialmentioning
confidence: 54%
See 2 more Smart Citations
“…For comparison, table 1 summarizes the important parameters of several films that are good candidate materials for magnetic recording and sensor applications. Obviously, the present films exhibit superior properties to the comparison films (table 1) and other films reported in the literature [10][11][12][13][14][15][16][17][18][19]. Among them, the P O2 = 11.5% sample (Co 19.35 Fe 53.28 Hf 7.92 O 19.35 ) exhibits the softest magnetic properties (4π M s = 19.86 kG and H cE = 1.5 Oe) together with a high electrical resistivity (ρ = 3569 μ cm).…”
Section: Magnetic and Electrical Properties 321 Effects Of Partialmentioning
confidence: 54%
“…In this context, the recent findings of new magnetic oxide thin films are of practical importance in high-frequency applications because these materials can show a good highfrequency performance into the gigahertz range owing to their resistivity, which is approximately ten times higher than that of conventional magnetic alloy films [6,7,[10][11][12][13][14][15][16][17][18][19]. Hayakawa et al [10] first reported that Fe-M-O (M = Hf, Zr) magnetic films possessed a good magnetic softness owing to their nanostructure which consisted of ferromagnetic bcc nanocrystals (∼10 nm in size) embedded in an amorphous matrix containing large amounts of M and O elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its amorphous structure was confirmed before by x-ray scattering experiments, though with a phase separation occurring during the film deposition. 23 The first diffuse peak ͑not shown here͒ is thus slightly split, suggesting two interconnected amorphous phases with nearest atomic correlations dominated by Hf-O and Co-Co͑Fe͒, respectively. Nevertheless, the films show excellent soft magnetic properties with strong uniaxial magnetic anisotropy ͓see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the last decade, much research has been carried out to develop magnetic thin film with excellent high frequency characteristics for application to high-frequency devices such as perpendicular media, magnetic recording write heads and thin-film wireless inductor cores [1][2][3][4][5][6][7]. The highfrequency applications of magnetic thin films require the thin films to possess a high saturation magnetization and an appropriately large in-plane uniaxial anisotropy (IPUMA) [8][9][10][11] field to achieve a high cutoff frequency, which is the highest theoretically possible frequency of soft materials.…”
Section: Introductionmentioning
confidence: 99%